Why breast feeding fails. Issue 1 (21st December 2006) - Harris, V; Hall, D
Abstract : Background: Vanessa is a 34-year-old lawyer married to a police officer. Her first baby was born after a perfect pregnancy and labour until fetal distress necessitated an easy Ventouse extraction late in the second stage. Baby F had normal Apgar scores and weighed 2920 g. This paper records a conversation between Vanessa (V) and her father (F) about breast feeding.